Alpha-santalol, a derivative of sandalwood oil prevents development of prostate cancer in TRAMP mice - Ajay Bommareddy; John Oberlin; Kaitlyn Blankenhorn; Sarah Hughes; Erica Mabry; Aaron Knopp; Adam VanWert; Chandradhar Dwivedi; Isaiah Pinkerton; Linda Gutierrez (Elsevier, 2024)
Background: Alpha-santalol, a major component of sandalwood oil inhibits growth of cultured prostate cancer cells in vitro by causing apoptosis. However, its in vivo efficacy against prostate cancer development is not established. Hypothesis/purpose: Prostate cancer is one of the most commonly diagnosed cancers in men. The present study was undertaken to determine the in vivo efficacy of alpha-santalol using TRAMP (Transgenic Adenocarcinoma of Mouse Prostate) mice as a model. Methods: TRAMP mice were used for the in vivo studies. Immunohistochemical analysis was used to assess prostate/tumor sections and Ki-67 staining. Western blot analysis was used to determine expression of various proteins. TUNEL assay was used to detect apoptotic bodies. Results: Administration of alpha-santalol (100 mg/kg body weight) decreased the incidence of prostate tumors, average wet weights of urogenital organs and prostate weight compared to control mice. In addition, the area occupied by normal prostate was significantly higher, along with poorly differentiated carcinoma that was significantly lower in the dorsolateral prostate sections of alpha-santalol-treated mice compared with the controls. Furthermore, the dorsolateral sections of prostate from alpha-santalol-treated mice exhibited decreased cell proliferation (Ki-67 staining) in association with induction of apoptosis (TUNEL-positive cells). In agreement with immunohistochemical analysis, Western blotting analysis of prostate/tumor samples from alpha-santalol-treated group revealed a decrease in survivin, XIAP, PCNA, cyclin D and CDC2 levels compared to control samples. Conclusion: The present study shows for the first time, that alpha-santalol administration inhibits the development of prostate cancer in TRAMP mice by decreasing cell proliferation and inducing apoptosis, and warrants future studies for its clinical development.